Dysfunctional Finance : Positive Shocks and Negative Outcomes - Hoff, Karla (2012)
n financial markets with asymmetric information about mean returns, borrowers with different default risks may pay the same rate of interest. If they do, the marginal borrower will have a high-risk, negative-value project. Under some conditions, technological change that increases each entrepreneur's output will attract a new set of negative-value projects. This adverse selection process will erode the ability rents of the inframarginal borrowers. I present an example in which it destroys the market. The results imply that a boom in a sector can lead to a crisis if institutional change to solve the screening problem does not occur.